The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/ajmg.b.30694
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and overweight associate with non‐APOE4 genotype in an alzheimer's disease population

Abstract: Type 2 diabetes is a risk factor for late-onset Alzheimer's disease (AD), and studies suggest that pathogenic effects of diabetes and insulin resistance may be associated with non-APOE4 AD. Therefore, we examined association of the APOE4 allele with diabetes in an AD population. Retrospective and cross-sectional clinical and APOE-genotype data on 465 cases with probable or definite AD previously ascertained by the National Institute of Mental Health Genetics Initiative were analyzed by regression analysis. Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
2
16
0
2
Order By: Relevance
“…There has been evidence that ApoE ε4 negative individuals are more sensitive to the cognitive consequences of insulin resistance [15, 24] and that a relationship between insulin resistance and dementia risk may be most commonly observed for adults without an ε4 allele [38, 39]. Our current results further extend this finding to suggest that the ApoE ε4 gene interacts with sex to moderate treatment response.…”
Section: Discussionsupporting
confidence: 77%
“…There has been evidence that ApoE ε4 negative individuals are more sensitive to the cognitive consequences of insulin resistance [15, 24] and that a relationship between insulin resistance and dementia risk may be most commonly observed for adults without an ε4 allele [38, 39]. Our current results further extend this finding to suggest that the ApoE ε4 gene interacts with sex to moderate treatment response.…”
Section: Discussionsupporting
confidence: 77%
“…Further, levels of senile plaques and neurofibrillary tangles were highest in obese men that were also APOE 4 carriers (Peila et al, 2002). However, several other studies reported that the AD risk associated with obesity and metabolic syndrome is stronger in APOE 3 carriers (Dixit et al, 2005; Leiva et al, 2005; Singh et al, 2006; Profenno and Faraone, 2008). …”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, APOE 4 carriers can be more sensitive to metabolic consequences associated with obesity (de-Andrade et al, 2000; Kypreos et al, 2009; Niu et al, 2009; Atabek et al, 2012; Zarkesh et al, 2012; Guan et al, 2013). Although some studies do not report an APOE 4 bias in obesity-associated AD risk (Profenno and Faraone, 2008; Luchsinger et al, 2012), others have found that AD risk is increased by obesity (Peila et al, 2002; Ghebranious et al, 2011) and diets high in calories and fatty acids (Luchsinger et al, 2002) only in APOE 4 carriers. Though the human literature suggests a gene-environment interaction between APOE and obesity in regulating development of AD, this question has not been addressed in experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…Although they may appear as disparate conditions, the risk of Alzheimer’s disease, AD, is increased by middle age obesity, type II diabetes, and cardiovascular/cerebrovascular disease123456789101112131415161718192021, suggesting that a common mechanism of pathophysiology may exist between these conditions. For example, amyloid precursor protein, APP, cleavage to generate the aggregate-prone amyloid beta, Aβ, peptide is a hallmark of the senile plaque pathology of sporadic late onset and early onset AD22.…”
mentioning
confidence: 99%